STUDI KOMPARASI KONSEP CINTA DALAM PANDANGAN ARTHUR SCHOPENHAUER DAN SØREN AABYE KIERKEGAARD (Studi Reflektif terhadap Fenomena Bunuh Diri Atas Dasar Cinta) - Zhafira, Annisa Ranah; Siswadi, Gede Agus (Jawa Dwipa, 2024)
This research aims to examine and compare the concept of love in the views of two great philosophers, Arthur Schopenhauer and Søren Aabye Kierkegaard, and relate it to the phenomenon of suicide caused by love. Love is often perceived as something beautiful because it involves deep feelings of affection, emotional closeness, and genuine attachment between individuals. Love is also described as a source of happiness, inspiration, and meaning in life. It brings people together, creates warmth, and provides invaluable emotional and moral support. Love also encourages individuals to act selflessly, sacrifice for the good of others, and grow into a better person. This research uses a qualitative method with a phenomenological approach and text analysis. The results of this study show that Schopenhauer, with his pessimistic view, sees love as a manifestation of the irrational and selfish will to live, which often leads to suffering. Romantic love is an illusion created by the will to preserve the species, so disappointment in love can be very destructive, leading to feelings of despair and acts of suicide. In contrast, Kierkegaard, with his existentialist and religious approach, views love as an expression of subjectivity and individual decision that involves commitment and sacrifice. True love requires a leap of faith and a courageous decision, where failure in love can reflect a deep existential crisis.